ANALYSIS OF PRISONERS' MOTIVATION IN PARTICIPATING IN INDEPENDENCE DEVELOPMENT ACTIVITIES AT CLASS IIA KUNINGAN CORRECTIONAL FACILITY - Slamet, Agung Maulana; Rifani, Denny Nazaria (Universitas Nusa Cendana, 2025)
The low motivation of inmates of Class IIA Kuningan Correctional Facility in participating in the independence coaching program. This study aims to determine the motivation of prisoners in participating in independence coaching activities as a strategy to increase prisoner motivation. This research uses a qualitative method by analyzing the data obtained from interviews and observations made at the Kuningan Class IIA Prison. Data collection techniques using primary sources and secondary sources. The results showed that prisoners who are motivated by independence coaching activities are prisoners who have the desire to move forward so that they have certainty of the future, while unmotivated prisoners are due to a lack of willingness to move forward and do not know what kind of conditions they want after the prison term is over. Keywords: Prisoners; Motivation; Independence; Development